A framework for interpreting the right to freedom of association of workers and trade unions in European human rights law - Arabadjieva, K (2019)
The right to freedom of association, as a labour right, has long been protected by Conventions 87 and 98 of the International Labour Organization, and by the European Social Charter. The European Convention on Human Rights and European Union law have more recently emerged as sources of protection of collective labour rights. This thesis identifies a particular concern arising from this development, namely that ECHR and EU norms that diverge from and conflict with ILO and ESC freedom of association guarantees could displace and undermine the authority of the latter, specialist mechanisms, which provide an overall higher level of protection. This thesis proposes that this concern could be addressed to a significant extent through the interpretation of ECHR and EU freedom of association guarantees in closer alignment with ILO and ESC norms. It first argues that there is a normative, moral justification for convergence between ECHR and EU human rights norms, and ILO and ESC specialist labour law norms. On this basis, it proposes that in interpreting ECHR and EU freedom of association guarantees, the respective Courts should look to ILO and ESC norms as key sources of authority; and that a divergent interpretation of these norms should be justified on the basis of appropriate reasons. These could be reasons pertaining to the text or aims of the relevant instruments and legal systems, particular institutional characteristics, or the fact that the ECHR and EU enforcement bodies are courts and not committees. The analysis concludes that the institutional concern cannot be completely resolved through the interpretation of ECHR and EU freedom of association guarantees in line with ILO and ESC norms, since differences between norms are sometimes well-justified. Nevertheless, the proposed interpretive framework could go significant distance towards achieving this goal, and make a substantial contribution to strengthening the protection of collective rights in Europe.